The innovation challenge in micro and small enterprises (MSE) - Davi França Berne; Roberto Coda; Patricia Krakauer; Denis Donaire (Innovation & Management Review, 2019)
Purpose - This study aims to measure the degree of innovation of micro and small industrial companies in the West and Southwest metropolitan regions of the city of S\~ao Paulo, through a survey with 203 firms in the metallurgy sector. Design/methodology/approach The research had a quantitative and descriptive focus and used as methodology the validated and international approach known as Innovation Radar. Findings The degree of innovation in these micro and small companies is low; thus, the authors could not characterize them as systemic innovators. Most of them are little innovative, although some were classified as occasional innovators. The dimensions organization, processes, presence, supply chain and added value were the least developed. Research limitations/implications To carry out similar studies in other Brazilian regions, to compare results and draw new conclusions, or even check if the degree of innovation present in micro-firms of these regions would not be even lower; to monitor the evolution of companies through a longitudinal study, to detect improvements in the degree of innovation; and to conduct a qualitative research that can deepen questions on the results of our study, such as the reasons why this type of company does not adopt innovative practices, or even the real suitability of the Innovation Radar model for micro and small enterprises (MSEs). We observed that some dimensions proved to be too sophisticated for these companies, such as R&D investments and the adoption of technological advances. Practical implications The study shows that the degree of innovation measured by the Innovation Radar is a useful and initial measure to check an innovative attitude in micro and small companies. It can also drive the actions that should be prioritized to stimulate the culture of innovation in SME. However, it does not allow to answer why this type of organization does not adopt innovative practices as a management attitude. Regarding its contribution, the authors expect that the paper may bring an awareness of managers and owners of micro and small companies for the need to foster innovative practices that can help increase the competitiveness and survival of this type of organization. Social implications In Brazil, despite the fact that MSEs represent 98 per cent of the existing companies, and are mainly responsible for job creation, their leaders have a low concern for innovative practices. Originality/value The study contributes to identify the degree of innovation of these firms, which comprise a representative and strategic segment of the city's economy, by checking to what extent an innovative attitude is effectively present in this sector. The theoretical contribution of this study regards the appropriateness of mechanisms or methodologies created to measure the degree of innovation in large organizations. Dimensions such as technological platform, brand, innovative ambience, degree of organization or systematization of processes, which are frequently considered for companies in general, and especially for large ones, are not sufficient or, instead, too sophisticated to allow an effective measurement of the degree of innovation in MSE. Thus, this study provides information for designing more effective ways to evaluate the degree of innovation that take into account MSE's specificities, which can be considered innovation efforts, such as simple process improvements, professional development of teams, and actions to seize ideas and opportunities, among others.
Keywords: 650; Innovation; Degreeofinnovation; Micro and small enterprise